The impact of dance as a non-pharmacological adjuvant therapy cancer survivors: a clinical trial (Research, Society and Development, 2022)
This study aimed to investigate the impact of dance as a non-pharmacological adjuvant therapy on the quality of life (QoL), pain sensation, and depression of female cancer survivors. Method: We conducted a parallel, open-label, randomized, controlled clinical trial where cancer patients were invited to experience dance as a language. The intervention comprised two dance group classes per week for 20 weeks involving creative dance processes and light to moderate physical exercises. The participants were randomized into two groups – control (did not undergo the dance classes) and intervention (underwent the dance classes) – and answered questionnaires before, during, and after the intervention. We assessed the QoL (Functional Assessment of Cancer Therapy General), pain perception (Visual Analog Scale and McGill Pain Questionnaire), and depression (Hamilton Depression Rating Scale). Results: The statistical data analyses revealed that the intervention and control groups did not present statistical differences in age, cancer type, stage of disease, surgical treatment, and scapular and pelvic involvement. The results showed an improvement in the intervention group’s QoL regarding the affective, miscellaneous, sensory, and total dimensions and decreased pain perception and depression. Conclusion: This clinical trial presented dance as a complementary non-pharmacological adjunct therapy for cancer survivors' treatment, improving quality of life and decreasing pain perception and depressive processes. Implications for cancer survivors: The practice of dance as a language is a valid intervention to help female cancer survivors face the disease's physical and psychosocial effects.